Transcriptional profiling of milk fat synthesis in mammary gland of dairy cows with different forage quality using RNA sequencing - Zhang, Hang; Ao, Changjin; Khas-Erdene,; Dan, Ni (Frontiers in Veterinary Science, 2025)
IntroductionThis study was designed to determine the effects of diets containing different-quality forages and concentrate content on milk composition and lipogenic enzyme expression in the mammary glands of dairy cows using RNA sequencing.MethodsThirty Holstein cows were randomly assigned to one of three treatments: mixed forage consisted of hay, silage, and alfalfa forage to a concentrate ratio of 54:46 (MF); corn stover as forage and forage to a concentrate ratio of 35:65 (CSA); corn stover as forage and forage to a concentrate ratio the same as MF (CSB). Mammary tissue biopsies were performed to analyze lipogenic enzyme expression using RNA-seq.ResultsTreatments did not affect dry matter intake, milk protein, or lactose. The milk yield, fat content and saturated fatty acids (SFAs), and short- and medium-chain fatty acids (SMFAs) contents were lower in CSA and CSB than in MF. Still, the unsaturated FA and long-chain FA contents were higher than in MF. We used RNA-seq to compare analyses of three groups of mammary tissue in transcriptomics, Gene Ontology and KEGG-enriched pathways. Differentially expressed genes (DEGs) involved in lipid metabolic pathways and the FA biosynthesis pathway in MF were significantly higher than in CSB. In contrast, DEGs of FA extension and unsaturated FA synthesis pathway were significantly lower than in CSB.ConclusionCorn stover as a forage diet reduced the milk yield, fat content, SMFAs, SFAs, and the gene expression of mammary lipogenic enzymes in dairy cows.